Migration and social protection : claiming social rights beyond borders - Sabates-Wheeler, Rachel; Feldman, Rayah (Palgrave Macmillan, 2011)
The growing scale of international migration has reshaped the debate on the social rights and social protection available to people outside their countries of origin. This book uses conceptual frameworks, policy analysis and empirical studies of migrants to explore international migrants' needs for and access to social protection across the world.